Дослідження впливу мікрохвильового опромінення на деякі гідробіонти - Григорьева, О.О.; Вакуленко, О.В. (Біополімери і клітина, 2004)
Вивчено вплив мікрохвильового опромінення дециметрового діапазону з частотою 2450 МГц (довжина хвилі 12 см) на деякі гідробіонти тваринного та рослинного походження. Проаналізовано виживаність пуголовків жаби ставкової Raw esculenta і личинок комарів Culex pipiens molestus Forskal, а також швидкість руху протоплазми клітин Vallisneria spiralis L. під впливом електромагнітної радіації. In this paper, the influence of microwave irradiation of decimeter range with the frequency 2450 MHz (wavelength 12 cm) on some hydrobionts including objects of animal and vegetable origin, was investigated. We studied the vitality of tadpoles of Rana esculenta, gnats of Culex pipiens molestus Forskal, and movement velocity of protoplasm of cells of Vallisneria spiralis L. under influence of electromagnetic radiation. It was shown that radiation has mainly thermal influence on the vitality of animals, though the critical temperature of radiation heating is lower than that of ordinary heating. The cumulative effect of the microwave radiation of the decimeter range was not observed. The vegetables displayed more stability to radiation than the animals. Изучено влияние микроволнового облучения дециметрового диапазона (длина волны 12 см) с частотой 2450 МГц на некоторые гидробионты животного и растительного происхождения. Интенсивность влияния электромагнитного облучения определяли по жизнестойкости головастиков Ranaes culenta, личинок комаров Culex pipiens molestus Forskal и по скорости движения протоплазмы клеток Vallisneria spiralis L. Показано, что сверхвысокочастотное облучение имеет преимущественно тепловое действие. Накопительный эффект радиации в данном диапазоне не обнаружен. Растительные объекты оказались более стойкими к облучению по сравнению с животными.